2018
DOI: 10.1093/jas/sky080
|View full text |Cite
|
Sign up to set email alerts
|

Identification of redox imbalance as a prominent metabolic response elicited by rapeseed feeding in swine metabolome1

Abstract: Rapeseed (RS) is an abundant and inexpensive source of energy and AA in diets for monogastrics and a sustainable alternative to soybean meal. It also contains diverse bioactive phytochemicals that could have antinutritional effects at high dose. When the RS-derived feed ingredients (RSF) are used in swine diets, the uptake of these nutrients and phytochemicals is expected to affect the metabolic system. In this study, 2 groups of young pigs (17.8 ± 2.7 kg initial BW) were equally fed a soybean meal-based contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…coli [41]. Interestingly, the metabolomics analysis performed on the present study did not detect any significant increase in SCFA concentrations in the digesta of RSF-fed pigs [18]. However, microbiota profiling found that the bacterial phylotypes reputed to be responsible for dietary fiber fermentation and SCFA production were more abundant in RSF pigs.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…coli [41]. Interestingly, the metabolomics analysis performed on the present study did not detect any significant increase in SCFA concentrations in the digesta of RSF-fed pigs [18]. However, microbiota profiling found that the bacterial phylotypes reputed to be responsible for dietary fiber fermentation and SCFA production were more abundant in RSF pigs.…”
Section: Discussionmentioning
confidence: 58%
“…In our study, stronger negative correlations were found between the bile acids and the bacterial genera in the RSF pigs compared with the CON pigs in colon. Previously, no significant difference in bile salt concentrations between the CON and the RSF diets was observed [18]. However, the negative associations between the bacteria and bile salts in colon of the RSF pigs are interesting and should be studied further in terms of health-promoting effects of RSF because secondary bile acids (e.g.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This also indicated that microbial function between t0 and later time points was modulated, and geared toward degradation of these new substrates. Previous studies showed that a high-fiber rapeseed diet did not results in a significant increase in SCFA content in the chyme of RSM-fed pigs after a 3-week adaptation period ( Chen et al, 2018 ; Umu et al, 2018 ), which seemed to indicate that the adaptation period was not long enough. Thus, strategies should be considered to shorten the fiber adaptation period, in order to increase feed efficiency.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies showed that a high-fiber rapeseed diet did not results in a significant increase in SCFA content in the chyme of RSM-fed pigs after a 3-week adaptation period ( Chen et al, 2018 ; Umu et al, 2018 ). However, SCFA-producing microbes, such as Dialister , Shuttleworthia , Bulleidia , Coprococcus , and Lachnospira , were detected more abundant in the colon of high-fiber rapeseed pigs compared to those in the control pigs ( Umu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 96%